Determinants of Generation Z Green Investment Interest: The Role of Social Media Platforms as Moderating Variables - Nilasari, Priyanti Dewi; Fitriyah, Fitriyah (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
Green investment interest is a response to increasing greenhouse gas emissions that have the potential to damage the sustainability of life on Earth. This study aims to analyze elements that can increase Generation Z's green investment interest in Malang City, with social media platforms as moderating variables. The study used quantitative methods with Cochran's Formula technique to identify a subset of 100 respondents from Within the study from four state universities in Malang City. Structural Equation Modeling-Partial Least Square is the test tool used in this study The significance between independent variables on green investment interest in Generation Z in Malang City was estimated through WrapPLS 7.0 software. The results showed that attitude, behavioral control, and green investment knowledge significantly positively affect green investment interest, while subjective norms are not positively insignificant to Generation Z's green investment interest. Social media platforms strengthen the relationship between attitude and knowledge of green investment interest.  However, Generation Z's green investment interest in Malang City, which is influenced by subjective norms and behavioral control, cannot be strengthened by the existence of social media platforms.